Pengaruh Variasi Suhu dan Lama Penyimpanan terhadap Viabilitas Bakteri Asam Laktat (BAL) dan Nilai pH Yoghurt - Aditya Dimas Pangestu; Kurniawan Kurniawan; Supriyadi Supriyadi (Borneo Journal of Medical Laboratory Technology, 2021)
Consuming yogurt indicates the increasing public awareness of healthy lifestyles has led many people to consume yogurt. Yogurt is a fermented milk product by adding pasteurized skim milk concentrate and adding lactic acid bacteria culture. L. casei is the bacterial culture commonly used in the production of yogurt, which has a role in breaking down lactose into lactic acid. To maintain its quality, yogurt is generally stored at a low temperature. However, there are still many business actors who only store it in a cool box or even at room temperature. The purpose of this study was to describe the viability of LAB and the effect of variations in temperature and storage time on the viability of LAB and pH value of yogurt. This study used an experimental method with a completely randomized design (CRD) with 3 treatments in the form of variations in storage temperature, namely 5°C, 15°C, and 25°C, each treatment temperature was stored for 1 week, 2 weeks, 3 weeks, and 4 weeks. This study was conducted in December 2020. The results showed that the highest viability value (289x106 CFU/mL) of lactic acid bacteria in yogurt was obtained at 5°C with two weeks of storage. Yogurt's pH value is influenced by temperature and storage time; the higher the temperature and storage time, the causes the yogurt's pH value decreases. The conclusion that can be drawn from this study is that the highest viability of LAB was obtained at 5°C with a shelf life of two weeks, while the best pH value of yogurt was achieved at 5°C for one week.